In vitro cytotoxic and anti-inflammatory activity of Bruckenthalia spiculifolia extracts and fractions - Pavlović, Dragana; Stojanović, Nikola; Zlatković, Bojan; Radulović, Niko; Kovačević, Nada (Archives of Pharmacy, 2022)
According to our previous studies, Bruckenthalia spiculifolia Rchb. (Ericaceae) possess strong antioxidant activity and hydrogel loaded with 2% ethanolic extract from its flowers and leaves is a potential southing and wound healing agent. Ethanolic extracts of leaves, flowers, and herba, alongside fractions obtained by systematic solvent extraction method with solvents of the increasing polarity of liquid-liquid fractionation of areal parts of B. spiculifolia, were prepared. To estimate in vitro anti-inflammatory activities of eight different extracts and fractions, isolated rat peritoneal macrophages were employed. MTT test was used for the cytotoxicity determination, while the anti-inflammatory potential lipopolysaccharide-induced NO production model was utilized. Experimental procedures with animals complied with the rules of the European Union Normative. Resident rat peritoneal macrophages were harvested by peritoneal lavage and used for both procedures. Phytochemical analysis was done by RP-HPLC coupled with DAD detection. Tested samples statistically significantly decreased macrophage ability to metabolize MTT, mainly in a concentration-dependent manner. All of them also significantly inhibited NO production from macrophages stimulated with lipopolysaccharide, which can be related to either their cytotoxic or anti-inflammatory activity. Quantified polar compounds (especially quercetin-3-O-glucoside) could be associated with better antioxidant and anti-inflammatory effects, as well as with a lower cytotoxic potential. Indeed, fractions obtained with ethyl acetate and water, but also ethanol extract obtained after lipids removal with petroleum ether, showed the most promising effects. These results point out that B. spiculifolia is worth further investigation in order to detect new naturally occurring anti-inflammatory agents.